Single-crystalline ZnO nanobelts by RF sputtering - Supab Choopun (2018)
ZnO nanobelts were synthesized by RF sputtering on copper substrates. The sputtering time was 60 min, in an argon atmosphere at a pressure of 40 mTorr, and with RF power set at 300 W. The obtained ZnO nanobelts exhibit a single-crystalline hexagonal structure with a thickness, width and length of about 10, 50 nm, and several micrometers, respectively. The TEM analysis suggested that the ZnO nanobelts grew along the [112̄0] and [21̄1̄0] directions on (0 0 0 1) plane. These ZnO nanobelts have a potential application for use as a nanogas sensor. © 2005 Elsevier B.V. All rights reserved.